Processing of Chloride-Containing Productive Solutions after Uranium in situ Leaching by Ion Exchange Method - Svetlana Titova; Sergey Skripchenko; Alexey Smirnov; Vladimir Rychkov (Universitas Gadjah Mada, 2019)
The uranium sorption from productive solutions containing chloride ions using anion-exchange resins was investigated. The VPAE ion exchanger had the highest values of the sorption capacity, which for the experiment in the static mode was 13 kg U m-3, and for the experiment in the dynamic mode, it was equal to 36 kg U m-3. The use of VPAE anion exchanger will make it possible for uranium recovery from productive solutions with an increased content of chloride without sacrificing the productivity of the sorption plant. The process of saturated resins regeneration by various reagents was investigated. The use of ammonium nitrate solution with sulfuric acid ensured maximum value of uranium recovery from the saturated resin phase (76–97%).